ISLAM AGAMA TEROR? (ANALISIS PEMBINGKAIAN BERITA MEDIA ONLINE KOMPAS.COM DALAM KASUS CHARLIE HEBDO) - Ismail Fahmi Arrauf Nasution; - Miswari (al-Balagh : Jurnal Dakwah dan Komunikasi, 2017)
Mass media is an effective instrument in shaping public opinion. Though mass media is believed to be principally transparent and independent, the information presented to the public is the result of human construction based on their understanding of the reality of knowledge. In this topic, majority of Moslem, recently, claim that some popular mass media are not objective in reporting terrorism. For that reason, this article efforts whether the image of Islam as a religion of terror is constructed, especially from the online media framing in Kompas.com about the incident in Charlie Hebdo’s media in Paris.